Microsphere-based interferometric optical probe - Yongjae Jo (Nature Portfolio, 2018)
Tagging and tracking cells with multiplexed labels can help study complex cellular behaviors in living systems. Here, Jo et al. propose and demonstrate the use of Fabry-Perot-like resonances in dielectric microspheres as such a label and call these reflectophores.